FOCUS GROUP DISCUSSION AND QUANTITATIVE SENSORY ANALYSIS TO IDENTIFY SENSORY PARAMETERS OF NEW FOOD PRODUCT - Christianus Jodi Yonathan; Yoga Pamudya Gunawan Ristam; Vania Aurellia Wijaya; Oki Krisbianto (School of Tourism, Universitas Ciputra Surabaya, 2021)
Focus Group Discussions (FGD) is a renowned method for new food product development. This research used FGD followed by Quantitative Descriptive Analysis (QDA) and Affective Test (AT) to identify the sensory parameters of pineapple wine. Based on FGD, five parameters were found to be crucial for panelists while testing the wine, i.e. distinctive pineapple aroma, sweetness, alcoholic flavor, alcoholic taste and appearance. These five parameters were then used in QDA and AT to understand the expectation of panelists on the sample which was served. It was found that FGD, QDA and AT were effective in identifying the sensory parameters of pineapple wine